Qanilaarneq (Closeness/Being Close) as a Desired State: Mediating Conflict Through Storytelling in Kalaallit Nunaat (Greenland) - Chahine, Anne S. (Études Inuit Studies, 2023)
This paper focuses on storytelling as a site for knowledge creation and meaning making to better understand how relationships are established and community is made in Kalaallit Nunaat (Greenland). The basis of this article is a selection of stories created by young Kalaallit (Greenlandic Inuit) adults as part of a research project engaging in future memory work, where participants were asked to create “future memories” for subsequent generations by producing stories that best represent what they consider to be worth preserving. Connecting these stories are the storytellers’ evocations of solidarity, care, and responsibility, gesturing to other members of the Kalaallit community. Rather than centering on the stories’ content, I conceptualize their intent through a focus on storytelling as a social activity. I argue that the young Kalaallit I worked with seek to mediate conflict and mend rifts in society through their storytelling practice, envisioning a future state of Kalaallit community relations that is “closer” in nature, and I propose the Kalaallisut term “qanilaarneq” (closeness/being close) as a metaphor to think with and make this notion more tangible. Cet article se concentre sur le récit comme terrain de création de savoirs et de recherche de sens pour mieux comprendre comment les relations et les communautés se forment à Kalaallit Nunaat (Groenland). Cet article se base sur une sélection de récits créés par de jeunes adultes Kalaallit (Inuit groenlandais) dans le cadre d’un projet de recherche axé sur le travail de la mémoire du futur, où des participants étaient appelés à créer des « mémoires futures » pour les prochaines générations en produisant des récits qui représentent ce qui devrait, selon eux, être préservé. Le fil conducteur qui relie ces récits sont les thèmes évoqués par les narrateurs, notamment la solidarité, le soutien et la responsabilité, des gestes posés envers les autres membres de la communauté Kalaallit. En lieu de centraliser les contenus de ces histoires, je conceptualise leur ...